ТЕОРЕТИЧНІ ОСНОВИ ВИКОРИСТАННЯ ДИСТАНЦІЙНОГО НАВЧАННЯ У МЕТОДИЧНІЙ ПІДГОТОВЦІ МАЙБУТНІХ ВЧИТЕЛІВ ТЕХНОЛОГІЙ - Малихін, Андрій (Збірник наукових праць Уманського державного педагогічного університету, 2020)
У статті розглядаються теоретичні основи використання дистанційного навчання в умовах методичної підготовки майбутнього вчителя технологій. Зокрема, визначаються особливості використання інформаційно-комунікаційних технологій у дистанційному навчанні, якими є далекодійність, паралельність, гнучкість, синхронність, асинхронність, визначаються основні елементи дистанційної освіти. Також у статті дається характеристика засобам реалізації сучасного дистанційного навчання, визначаються особливості організації різних видів занять в умовах організації дистанційного навчання, розглядаються психолого-педагогічні особливості організації навчального процесу в системі дистанційного навчання майбутніх вчителів технологій, також вказуються переваги дистанційного навчання в умовах сучасного вишу. В статье рассматриваются теоретические основы использования дистанционного обучения в условиях методической подготовки будущего учителя технологий. В частности, определяются особенности использования информационно-коммуникационных технологий в дистанционном обучении, какими являются взаимодействие на больших расстояниях, параллельность, гибкость, синхронность, асинхронность, определяются основные элементы дистанционного образования. Также в статье дается характеристика средствам реализации современного дистанционного обучения, определяются особенности организации различных видов занятий в условиях организации дистанционного обучения, рассматриваются психолого-педагогические особенности организации учебного процесса в системе дистанционного обучения будущих учителей технологий, также указываются преимущества дистанционного обучения в условиях современного вуза. In article theoretical basics of use of distance learning in the conditions of methodical training of future teacher of technologies are covered. In particular, features of use of information communication technologies in distance learning what are possibility of interaction at long distances, parallelism, flexibility, synchronism, asynchrony are defined, basic elements of remote education are defined. In Article is determined the distance learning system is softwarehardware complex designed for learning management using network communications technologies to provide educational services to a wide range of the population. Also basic elements of distance learning are specified in article: it transmission media of information and methods which depend on the technical environment of exchange of information, is given the characteristic to implementers of modern distance learning which treat: e-book readers, training materials in networks, computer educational systems, video training materials, laboratory remote practical works, electronic libraries. Besides features of the organization of different types of occupations in the conditions of the organization of distance learning are defined: lectures, seminars, a practical training, laboratory researches, consultations psychology and pedagogical features of the organization of educational process in system of distance learning of future teachers of technologies are considered, advantages of distance learning in the conditions of modern higher education institution are also specified.